Prototype Design of Smart Home System using Internet of Things - Teddy Surya Gunawan; Intan Rahmithul Husna Yaldi; Mira Kartiwi; Nanang Ismail; Nor Farahidah Za'bah; Hasmah Mansor; Anis Nurashikin Nordin (Indonesian Journal of Electrical Engineering and Computer Science, 2017)
Smart home control system can be integrated into an existing home appliances to reduce the need for human intervention, increase security and energy efficiency. However, it is still an open problem due to difficulties such as network distance, signal interference, not user friendly, increased cost and power consumption. This paper reviews various topics on smart home technologies including control system, smart home network, smart home appliance and sensor technologies for smart home. In this research, the proposed prototype of home automation allows users to remotely switch on or off any household appliance based on Internet of Things (IoT) with the enhancement of solar charger. The smartphone and/or tablet replaces the manual use of personal computer without the need for high additional cost. This prototype uses four types of sensors i.e. PIR sensor, temperature sensor, ultrasonic sensor and smoke gas sensor for automatic environmental control and intrusion detection.